PENGARUH PENAMBAHAN MINYAK ZAITUN SAAT PEREBUSAN TERHADAP KADAR LIKOPEN PADA WORTEL - Christ Kartika Rahayuningsih (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Lycopene is an antioxidant carotenoid class of compounds found in many vegetables and fruits that are red and orange as carrots. Lycopene levels may be increased in the processing of the oil medium, but will decrease in the heating process such as boiling. Purpose of the experiment was to determine the effect of olive oil in the boiling process in maintaining the levels of lycopene in carrots. This study is experimental with quantitative analysis using spectrophotometric method with extraction at 10 carrot samples drawn at randomly in the districts Semampir Surabaya criteria carrots same size and color. Of the samples analyzed earned on average levels of lycopene in carrots boiled for + 10 minutes at 100 °C without the addition of olive oil amounted to 0.2633% and the average levels of lycopene in carrots boiled for + 10 minutes at 100 °C with the addition of 1 ml of oil Olive at 0.3236%, the addition of 2 ml of olive oil amounting to 0.4077%, the addition of 3 ml of olive oil amounting to 0.4904%. The results of One Way Anova analysis showed that the levels of lycopene in carrots increased with the addition of olive oil and the more olive oil is added when boiling, the higher the levels of lycopene in carrots.